“THE JAMU HERBS ILLUSTRATION CARD” KONSERVASI BUDAYA KESEHATAN MASYARAKAT INDONESIA DENGAN MEDIUM ILUSTRASI AUGMENTED REALITY - Cennywati Cennywati; Fransisca Retno; Iqbal Oemar (Universitas Multimedia Nusantara, 2019)
In the modern era, Jamu (traditional herbal medicine) is one of the illustrious Indonesian heritage, are packaged into sachets and mixed with various chemical compounds. The authors felt the need to conserve the traditional way of making Jamu, by using only natural resources, for the sake of the next generations. The research discusses the implementation of augmented reality technology to differentiate the main ingredients of Jamu, describing the philosophy of Life and Death phase behind them, detailing the way how to compound them and other trivia. Botany illustrations are utilized in the augmented reality, as it is believed to be the effective media to reach the younger audience.